DEVELOPMENT OF CONTEXTUAL-BASED THEMATIC TEACHING MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES GRADE V PUBLIC ELEMENTARY SCHOOL PERCONTOHAN KABANJAHE - RANI EPITA YK; DEDE RUSLAN; SUMARNO SUMARNO (CV KULTURA DIGITAL MEDIA, 2021)
The purpose of this study was to determine the development of contextual-based thematic teaching materials to improve student learning outcomes. The subjects in this study were 60 students of grade V-A and V-B Public Elementary School. The object of this research is contextual-based thematic teaching materials for fifth grade students of Public Elementary School Percontohan Kabanjahe. The teaching materials developed are student books. This research is a Research & Development (R&D) research with activities at each development stage. The results of this study are (1) the validity of teaching materials is in the valid category. The average value of the validity of students 'books was 4.16, the average language validity was 4.21, the validity of the feasibility of presenting students' books was 4.13 and the student learning outcomes test instrument was valid. (2) The practicality of teaching materials has met the criteria, namely the positive response of students reaches 85%. (3) The effectiveness of teaching materials has been effective in terms of classical student learning completeness, namely at least 85% of students who take part in learning are able to achieve a score of ≥ 75, where learning completeness Classical students reach 92%; (2) the increase in the average result of student learning outcomes increased by 0.5 in the medium category.